Upaya Peningkatan Aktivitas Atletik Siswa Dalam Pembelajaran Pendidikan Jasmani Dan Kesehatan Pada Siswa Kelas VI SDN Kertajaya IX Dengan Metode Demonstrasi - Masriah, Niah (Faculty of Medicine and Health Science, Universitas Islam Negeri Maulana Malik Ibrahim, 2018)
Student achievement, especially on physical education subject of sport and health is not separated from teacher role to design an effective learning system one of the teacher's effort to improve effective learning is by increasing student activity with various technique, that is by doing various learning by using approach method an activity-based athletic game in particular.This research is hopefully able to provide and develop in the study of learning alternatives that remain and can improve the quality of maximum learning outcomes, and can be used as a reference for subsequent research.Â Keywords : Athletic, Activity, Physical